2016
DOI: 10.1371/journal.pone.0149561
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Spot Photoscreener in Detecting Amblyopia Risk Factors in Chinese Pre-school and School Age Children Attending an Eye Clinic

Abstract: PurposeTo evaluate the effectiveness of Spot photoscreener in detecting amblyopia risk factors meeting 2013 the American Association of Pediatric Ophthalmology and Strabismus (AAPOS) criteria in Chinese preschool and school-age children.MethodsOne hundred and fifty-five children (310 eyes), aged between 4 to 7 years (5.74 ± 1.2 years) underwent complete ophthalmologic examination, photoscreening, and cycloplegic retinoscopy refraction. The agreement of the results obtained with the photoscreening and retinosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
5
35
0
Order By: Relevance
“…However, paired t-test revealed that both the photoscreeners tend to measure the SE with a mild myopic shift, −0.17 D for Spot and −0.12 D for SW800. Studies from other groups also reported myopic shift of the measurements from photoscreeners such as Spot (−0.49 D),8 PlusOptix A09 (−0.52 to −0.57 D)18 19 and plusoptiX A12C (−0.45 D) 20. This less hyperopic measurement could be expected by the pupil dilation.…”
Section: Discussionmentioning
confidence: 78%
“…However, paired t-test revealed that both the photoscreeners tend to measure the SE with a mild myopic shift, −0.17 D for Spot and −0.12 D for SW800. Studies from other groups also reported myopic shift of the measurements from photoscreeners such as Spot (−0.49 D),8 PlusOptix A09 (−0.52 to −0.57 D)18 19 and plusoptiX A12C (−0.45 D) 20. This less hyperopic measurement could be expected by the pupil dilation.…”
Section: Discussionmentioning
confidence: 78%
“…Data here are reported at poorer than 0.3 logMAR, 0.5 logMAR and 1.0 logMAR and referrals were made for children having habitual visual acuity worse than 0.3 logMAR, to balance benefits of referrals with the limited eye‐care resources available in Tonga. Standard refractive error thresholds for screening were used for reporting and referral (astigmatism > 1.50 D, hyperopia > 3.50 D, anisometropia > 1.50 D, myopia < −1.50 D), as well as device‐specific adjusted refractive cut‐offs recently recommended (astigmatism > 1.25 D, hyperopia > 2.375 D, anisometropia > 1.125 D, myopia < −2.00 D) …”
Section: Methodsmentioning
confidence: 99%
“…There were two articles without full text and most of them were recorded in the Embase database exclusively. After detailed assessment with eligibility criteria, 21 publications with a total of 5022 subjects were included in the final meta‐analysis . Details of the 21 articles are summarised in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have made efforts to optimise the referral criteria to increase the test accuracy of the screener for various versions. 37,41,51 However, based on this metaanalysis (Figure 9), it is hard to tell significant differences in the performance across the software versions. Statistical analysis according to the software versions was not done because there are too many versions used across the included studies and very limited sample sizes for each version.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation